G-quadruplexes promote the motility in MAZ phase-separated condensates to activate CCND1 expression and contribute to hepatocarcinogenesis - Wang, Wenmeng; Li, Dangdang; Xu, Qingqing; Cheng, Jiahui; Yu, Zhiwei; Li, Guangyue; Qiao, Shiyao; Pan, Jiasong; Wang, Hao; Shi, Jinming; Zheng, Tongsen; Sui, Guangchao (Nature communications, 2024)
G-quadruplexes (G4s) can recruit transcription factors to activate gene expression, but detailed mechanisms remain enigmatic. Here, we demonstrate that G4s in the CCND1 promoter propel the motility in MAZ phase-separated condensates and subsequently activate CCND1 transcription. Zinc finger (ZF) 2 of MAZ is a responsible for G4 binding, while ZF3-5, but not a highly disordered region, is critical for MAZ condensation. MAZ nuclear puncta overlaps with signals of G4s and various coactivators including BRD4, MED1, CDK9 and active RNA polymerase II, as well as gene activation histone markers. MAZ mutants lacking either G4 binding or phase separation ability did not form nuclear puncta, and showed deficiencies in promoting hepatocellular carcinoma cell proliferation and xenograft tumor formation. Overall, we unveiled that G4s recruit MAZ to the CCND1 promoter and facilitate the motility in MAZ condensates that compartmentalize coactivators to activate CCND1 expression and subsequently exacerbate hepatocarcinogenesis. G-quadruplexes (G4s) can recruit transcription factors to activate genes. Here, the authors revealed that G4s drive molecular motility in phase-separated condensates of MAZ and coactivators, leading to activated CCND1 expression in liver cancer.